Empowerment of Rheumatoid arthritis sufferers through anti-rheumatism geriatric classes - Isrofah Isrofah; Irine Dwitasari Wulandari (Universitas Muhammadiyah Magelang, 2023)
The elderly is at risk of experiencing degenerative diseases compared to young people, one of which is Rheumatoid Arthritis. Rheumatoid Arthritis is a degenerative disease of the joints that can cause pain and stiffness and is still a major health problem in the world today. The aim of implementing this program is to educate the public about the correct management of Rheumatoid Arthritis so that they can avoid the adverse effects of joint pain and swelling, relieve stiffness and prevent joint damage. This program is carried out in the form of education and anti-rheumatic gymnastics. The results of this community service show an increase in partners' knowledge about efforts to prevent Rheumatoid Arthritis after education and practice of anti-rheumatic gymnastics.